PFA‐100‐measured aspirin resistance is the predominant risk factor for hospitalized cardiovascular events in aspirin‐treated patients: A 5‐year cohort study. (21st October 2017) - Chen, H. Y.; Chou, P.
Summary: What is known and objective: Aspirin therapy is the clinical gold standard for the prevention of cardiovascular events. However, cardiovascular events still develop in some patients undergoing aspirin therapy. Many laboratory methods exist for measuring aspirin resistance. Using the platelet Function Analyzer (PFA)‐100 system, we aimed to determine the effect of aspirin resistance on hospitalized cardiovascular events (hCVE) in a 5‐year follow‐up cohort. We also sought to determine the impact of aspirin resistance on the relationship between common cardiovascular risk factors and cardiovascular hospitalization. Method: Aspirin resistance was evaluated in aspirin‐treated patients from the outpatient department. A total of 465 patients during a 5‐year follow‐up period were included in this study. The primary endpoint of the study was hospitalization for any acute cardiovascular event. The prevalence and associated risk factors of acute cardiovascular events were evaluated. Results and discussion: Aspirin resistance was prevalent in 91 (20.0%) of 465 patients. Prior hospitalization history of cardiovascular events was highly associated with aspirin resistance ( P  =   .001). At the 5‐year follow‐up, cardiovascular events were found to have developed in 11 patients (8 stroke and 3 myocardial infarction) who exhibited aspirin resistance (12.1%) and in 9 (4 stroke and 5 myocardial infarction) patients who did not exhibit aspirin resistance (2.4%) ( P  <   .001). At the 5‐year follow‐up, multivariate logistic regression analysis results showed a strong association between aspirin resistance and cardiovascular events (adjusted odds ratio 4.28; 95% CI: 1.64‐11.20; P  =   .03). What is new and conclusion: PFA‐100 measurements of aspirin resistance correlate with hCVE, as evidenced by both the past medical history and the 5‐year follow‐up. The logistic regression analysis results showed that aspirin resistance plays a larger role in hospitalized cardiovascular disease than do other cardiovascular risk factors. Abstract : Aspirin resistance measured by PFA‐100 highly correlate with past history of hospitalized cardiovascular events. After 5‐year follow‐up, the logistic regressive analysis results showed that aspirin resistance plays a larger role in hospitalized cardiovascular disease than do other cardiovascular risk factors.